2020
DOI: 10.1186/s12882-020-02171-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of malnutrition inflammation complex syndrome among patients on maintenance haemodialysis at Muhimbili National Hospital in Tanzania: a cross-sectional study

Abstract: Background Malnutrition, inflammation, and the combination thereof are predictors of poor outcomes in haemodialysis patients. Malnutrition Inflammation Complex Syndrome (MICS) is an accelerator of atherosclerosis and portends high mortality. Early recognition and treatment of MICS may help to improve the clinical outlook of such patients. This study investigated the prevalence of MICS and its associated factors among patients on maintenance haemodialysis at Muhimbili National Hospital (MNH) in Dar es Salaam, T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…We excluded patients with severe respiratory distress and those who were mentally incapacitated. This study included 160 hemodialysis patients who were part of the study done to determine the prevalence of MICS among patients on maintenance hemodialysis at Muhimbili National Hospital in Dar es Salaam, Tanzania [9].…”
Section: Study Population and Sample Sizementioning
confidence: 99%
See 1 more Smart Citation
“…We excluded patients with severe respiratory distress and those who were mentally incapacitated. This study included 160 hemodialysis patients who were part of the study done to determine the prevalence of MICS among patients on maintenance hemodialysis at Muhimbili National Hospital in Dar es Salaam, Tanzania [9].…”
Section: Study Population and Sample Sizementioning
confidence: 99%
“…Each of them graded from 0 (normal) to 3 (severe). MICS was defined as having MIS of 6 or above [9]. Dialysis adequacy was assessed using the Urea Reduction Ratio (URR) calculated as (Pre-dialysis urea − Post-dialysis urea) ÷ Pre-dialysis urea × 100%.…”
Section: Study Variablesmentioning
confidence: 99%
“…Several experimental studies have demonstrated the potent cytotoxic and procalcific Ca-phosphate crystals in the absence of fetuin-A [156,157] . A decrease in systemic fetuin-A increases systemic calciprotein particles and procalcification of calciprotein particles, thus promoting vascular calcification [158][159][160][161][162] .…”
Section: Discussionmentioning
confidence: 99%
“…Patients aged 18 years and above who were on maintenance hemodialysis therapy for at least 3 months were eligible for this study. Additional information regarding EPO use and laboratory tests for iron parameters (iron, ferritin, transferrin saturation) were collected for 160 participants who were part of the study that investigated the prevalence and correlates of MICS [14].…”
Section: Study Design Setting Population and Sample Sizementioning
confidence: 99%